Georgia : Technical Assistance Report-Report on the Producer Price Index and Residential Property Price Index Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to assist Georgia's National Statistics Office (Geostat) in developing a residential property price index and expanding coverage of the producer price index (PPI). The mission found that Geostat compiles a monthly PPI for industrial products. It covers mining and quarrying; manufactured products; and electricity energy, gas, steam, and hot water. PPI coverage of the services sector is currently limited to freight transport, and should be expanded to include additional services. The improved coverage of the PPI will facilitate the assessment of developments in the production and prices of services and provide more reliable indicators to derive estimates of GDP in constant prices.